(untitled) (Journal of Educational Sciences, 2016)
The article deals with issues related to organization of secondary, vocational and higher education in Canada, and describes Career Development Programs in Canadian schools. The authors underscore that in Canada the guidance and career education programs are intended to enable students to explore and assess their own strengths, needs, and interests and to investigate a broad range of opportunities as they pursue their educational pathways, and to make sound career choices. Guidance programmes in schools have traditionally been based, as in the USA, on the role of the guidance counsellor. It is guidance counsellors who develop career education curriculum in the classroom and deal with individual career planning for students. However, the service is somewhat elitist, catering largely to post-secondary bound students. Students who are not post- secondary oriented are likely to receive little guidance. Career information is very important.In Canada the federal government and the governments of provinces widely use Internet resources so that a person can get information on learning opportunities at any stage of his life, occupations, educational programs, and job opportunities in order to plan for, get and keep employment.All career information is available of Internet sites of the Ministries of Education and the Ministry of Human Resources and Employment.